Agency and judgment in the study of corruption: A systematic review from psychology - Sarmiento-López, Julián Camilo; Gutierrez-Romero, Mario Fernando; Bernal-Sandoval, Felipe Andrés (Universitas psychologica, 2025)
This article presents a systematic review of the psychological literature on corruption. Models, methodologies, processes, and factors involved in the study and understanding of moral judgment and agency in corruption scenarios were identified. Based on the analysis of 61 studies (2013–2024) using the PRISMA methodology and bibliometric tools, four thematic focuses were identified: bribery in experimental settings, the psychological impact of perceived corruption, individual predictors of corrupt intention, and culture, values, and institutional legitimacy. The findings show that corrupt decisions are not explained by rational calculation. This cognitive phenomenon links the interaction of moral emotions (shame), relational closeness between people, the perception of contextual elements (perceived risk, institutional legitimacy), and cultural and personal beliefs. It is concluded that the psychology of moral development does not present a unified model. This heterogeneity raises the question of integrating cognitive, affective, normative, and interdisciplinary dimensions to explain corruption. Este artículo presenta una revisión sistemática de la literatura psicológica sobre la corrupción. Se encontraron modelos, metodologías, procesos y factores implicados en el estudio y comprensión del juicio y la agencia moral en escenarios de corrupción. A partir del análisis de 61 estudios (2013–2024) mediante metodología PRISMA y las herramientas bibliométricas se identificaron cuatro focos temáticos: sobornos en contextos experimentales, impacto psicológico de la corrupción percibida, predictores individuales de intención corrupta, valores culturales y confianza institucional. Los hallazgos muestran que las decisiones corruptas no se explican por cálculo racional. Este fenómeno cognitivo vincula la interacción de emociones morales (vergüenza), la cercanía relacional entre las personas, la percepción de elementos contextuales (riesgo percibido, legitimidad institucional) y las creencias culturales y personales. Se concluye que la psicología del desarrollo moral no presenta un modelo unificado. Esta heterogeneidad dirige la pregunta por integrar dimensiones cognitivas, afectivas, normativas e interdisciplinares para explicar la corrupción.